(untitled) (VITAL, 2025)
Research and practice of ethnopharmacy can improve the health and quality of life of communities and reduce the need for industrialized products and is therefore an environmentally friendly alternative. The therapeutic use of cannabis in the context of self-care is an example of the university’s performance in ethnopharmacy.